Yellow fever impact on brown howler monkeys (Alouatta guariba clamitans) in Argentina: a metamodelling approach based on population viability analysis and epidemiological dynamics - Moreno, Eduardo S (2015)
Fil: Moreno, Eduardo S. Universidade Federal do Oeste do Pará, Santarém, PA; Brasil.